Art & sole : contemporary sneaker art & design - Intercity Design (Firm) (London : Laurence King, 2012)
Over the years the sneaker scene has exploded with artist and designer collaborations. This title explores and celebrates the creative side of sneaker culture showing the best and most original rarities and collaborations.
Originally published: 2008.
Includes index.
boek